The genus Hypoxis L. (Hypoxidaceae) in the East Tropical - Wiland-Szymańska, Justyna (Biodiversity: Research and Conservation, 2010)
A complete key with full descriptions and distributions of all known Hypoxis taxa found in the East Tropical Africa is presented in the monograph. The morphology of all species, subspecies and varieties is described, including such important taxonomic characters for this genus like tuber flesh color, tunic type, indumentum and seed testa sculpture. A succulent leaf structure is described for H. kilimanjarica var. prostrata. The anatomical studies were conducted as a part of taxonomical analysis. They have positively evaluated a taxonomic significance of leaf anatomy characters, such as succulent structure, occurrence of bulliform cells in epidermis outside the keel zone, type and distribution of trichomes. The studies of the Hypoxis leaf anatomy added new data concerning anatomical differentiation of the cataphylls and the inner leaves. Also differentiated mesophyll and simultaneous presence of different types of stomata on one leaf are reported. It has been shown that in some species mucilage canals are present in the inner leaves and that this character is not constant. The number of vascular bundles, which can be determined only on the basis of a leaf section, is useful only in species with a small number of veins, not increasing with a plant age. Because of lack of constancy in distribution, number of stomata accessory cells cannot be used as a diversifying character for the East African species of Hypoxis. The wax crystals are revealed to exist in many species of Hypoxis. The anatomical characters of scapes were also studied in a taxonomic context. A sclerenchyma distribution, as well as number of vascular bundles can be used for a species determination. The presence of sclerenchyma prevents the scapes from bending down after anthesis. The studies of phenology revealed that there are two groups of taxa, one with a resting period and the other without it. It is connected with a climate in which the species occurs. The study of distribution maps of the species occurring in the East Africa are provided for this area, as well as for their entire range. This new knowledge, along with a revision of literature data, led to a new conclusion as to a number of all Hypoxis species in Africa, which is now estimated to be 55. The revision demonstrates that distribution of many of the Hypoxis species is connected with White's phytochoria. It proves that not only South Africa, but also the Zambesian Region is a very important center of diversity of this genus. The number of endemic taxa of Hypoxis for the East Tropical Africa is very low, including only one species and one subspecies. Additionally, a study of vertical ranges of Hypoxis is presented. It reveals that most of the species in East Africa grow in the mountains and they show preferences of dispersal in particular altitudinal levels. The analysis of the vertical distribution within the entire ranges of different taxa has showed differences in the altitudinal position depending on the geographic location. The human influence on Hypoxis is studied in terms of their use in folk medicine and believes. Most of the species of Hypoxis survive quite well in East Africa, being a visible component of various types of grasslands. Some species however are under threat of extinction. This is due to their incapability of surviving in changed habitats, especially in shade of cultivated plants. Another threat is a large-scale collection of species believed to cure the HIV, or sold as a substitute of similar taxa, assumed to possess such qualities. The IUCN categories are proposed for the East African taxa of Hypoxis.